LABOUR CONTRACT AS A MEANS OF PROTECTION OF LABOUR RIGHTS OF PERSONS WITH DISABILITIES - Bodnaruk, Mykola; Козуб, Ирина (My University, 2020)
The article analyses a labour contract as a manifold phenomenon which, along with long established scientific research of labour law in Ukraine in the sphere of its essence and content as a regulator of labour relationships, is also a means of protection of labour rights of employees in general and employees with disabilities in particular. On the basis of the research the conclusion has been made that a labour contract being a means of protection of labour rights of employees is meant to facilitate the realization of social purpose of the labour law of Ukraine which is the protection and security of the labour rights of the employees as an economically weaker party of labour relationships along with achieving the best possible balance of interests of employers and employees. In order to achieve the set goal of legal regulation of labour relationships and recognizing the importance of a labour contract as a means of protection of labour rights of the employees, the lawmakers have determined in Article 9 of the Labour Code of Ukraine the provisions on declaring invalid of those terms of labour contracts which worsen the conditions of employees in comparison with those determined by the labour legislation.